Analysis of 6174delT Mutation in BRCA2 Gene by Mutagenically Separated PCR Among Libyan Patients with Breast Cancer - Lamia Elfandi; Ghada Said; Saleh Suleiman Saleh; Mohamed Marwan; Nabil Enattah (Archives of Breast Cancer, 2016)
Background: Breast cancer is the most common malignancy among women. It is estimated that 1 in 10 women worldwide is affected by breast cancer during their lifetime. In 5 to 10% of breast cancer patients, the disease results from a hereditary predisposition, which can be attributable to mutations in either of two tumor suppressor genes, BRCA1 and BRCA2 to a large extent. BRCA2 6174delT mutation constitutes the common mutant alleles which predispose to hereditary breast cancer in the Ashkenazi population with a reported carrier frequency of 1.52%. In this study, we investigated the presence of the 6174delT mutation of the BRCA2 gene in Libyan woman affected with breast cancer and compared the results with those of other population groups.